2001
DOI: 10.1007/s004030000205
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of epitopes on the BP180 ectodomain targeted by IgA and IgG autoantibodies in patients with the lamina lucida-type of linear IgA disease

Abstract: Linear IgA disease (LAD) is an autoimmune subepidermal blistering skin disease characterized by the linear deposition of IgA at the dermoepidermal junction. Serum from patients with LAD most commonly contains autoantibodies that are directed against the hemidesmosomal transmembrane glycoprotein BP180 (type XVII collagen). Various antigenic sites on the extracellular domain of this anchoring filament protein have been shown to be targeted by autoantibodies in different autoimmune bullous skin diseases, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…In a study by Georgi et al (17) BP915 was bound by IgA in 44% of lamina lucida-type LABD serum samples tested and by IgG in 33% of such samples (17). The authors concluded that the C-terminus of BPl 80 represents the primary target on the BPl 80 ectodomain for both IgA and IgG antibodies in the serum of LABD patients (17). Healing with scarring is characteristic of MMP but it is also found in some lamina lucida-type LABD patients ( 17,20).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In a study by Georgi et al (17) BP915 was bound by IgA in 44% of lamina lucida-type LABD serum samples tested and by IgG in 33% of such samples (17). The authors concluded that the C-terminus of BPl 80 represents the primary target on the BPl 80 ectodomain for both IgA and IgG antibodies in the serum of LABD patients (17). Healing with scarring is characteristic of MMP but it is also found in some lamina lucida-type LABD patients ( 17,20).…”
Section: Discussionmentioning
confidence: 94%
“…Some, however, carry autoantibodies against a 230-kDa antigen, as well as additional, as yet uncharacterized epidermal antigens (3,16). Some cases of LAGBD have been reported as LABD, even though they satisfy the criteria for diagnosis of LAGBD ( 17). Recent immunoserological studies detected circulating IgA and IgG autoantibodies specific for certain epitopes of BP180 in bullous pemphigoid and LABD patients (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, circulating IgA anti-BMZ antibodies are often observed in the other subepidermal blistering diseases [9,18] , and circulating IgG anti-BMZ antibodies represent a frequent finding in patients with LABD [19][20][21] . Thus, the search for circulating IgA antibodies in LABD seems to be neither sensitive nor specific for the diagnosis of the disease.…”
Section: Problems With the Definition Of Reliable Diagnostic Criteriamentioning
confidence: 99%
“…Biologie : plusieurs antigènes cible En immunotransfert, des immunoglobulines de type IgA sont dirigées surtout contre les antigènes de la pemphigoïde bulleuse (BP180 ou PB230) mais aussi contre d'autres constituants de la jonction dermo-épidermique, fibrilles d'ancrage (collagène VII) [9] une des 3 portions de l'ectodomaine de BP180, principalement la fraction qui correspond aux antigènes de 97 et 120 kDa [10], contre BP230, BP180. Les IgG, quand elles sont présentes, sont dirigées contre BP180 et BP 230 et contre le collagène VII.…”
Section: Examens Complémentairesunclassified